2022
DOI: 10.3390/gels8110720
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modifications of Normal and Waxy Potato Starches Affect Functional Properties of Aerogels

Abstract: Aerogels are of increasing interest because of their exceptionally large surface area, porous structure, and low weight. Despite the significant increase in interest in the subject of starch-based aerogels, the number of detailed studies is rather scarce, which is especially evident in the case of chemically modified derivatives. Therefore, the study aims to evaluate the physicochemical properties of aerogels from chemically modified potato starch preparations (E 1422 and E 1450) obtained both from normal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Factors that affect the properties of hydrogels, such as AC and starch modification, also have an impact on the characteristics of aerogels. 97 In the study conducted by Le Thanh-Blicharz et al , 98 the physicochemical properties of aerogels prepared from normal potato starch (PPZ Trzemeszno, Trzemeszno, Poland) and waxy potato starch (“Eliane 100”, Avebe, Veendam, The Netherlands) were evaluated. It was observed that the waxy-starch-based aerogel had a higher bulk density (0.33 g cm −3 ) than the normal-starch-based aerogel (0.18 g cm −3 ).…”
Section: Starch-based Aerogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors that affect the properties of hydrogels, such as AC and starch modification, also have an impact on the characteristics of aerogels. 97 In the study conducted by Le Thanh-Blicharz et al , 98 the physicochemical properties of aerogels prepared from normal potato starch (PPZ Trzemeszno, Trzemeszno, Poland) and waxy potato starch (“Eliane 100”, Avebe, Veendam, The Netherlands) were evaluated. It was observed that the waxy-starch-based aerogel had a higher bulk density (0.33 g cm −3 ) than the normal-starch-based aerogel (0.18 g cm −3 ).…”
Section: Starch-based Aerogelsmentioning
confidence: 99%
“…In terms of oil absorption capacity, it also depends on the microstructure of aerogels. 98 In a recent study, microcrystalline cellulose aerogels were synthesized with different amounts of high amylose corn starch (0%, 5%, 10%, 15%, and 20%) and NaOH–urea solution using vacuum freeze-drying technology. 124 With an increase in starch content, the density of aerogels showed a trend of initially increasing and then decreasing, as did the adsorption capacity for linseed oil.…”
Section: Starch-based Aerogelsmentioning
confidence: 99%
“…The industry already produces chemically modified starch derivatives by the surface modification of starch granules [44,45]. Modified starch is prepared by physically (gelatinization, extrusion, foaming, and impregnation), chemically (esterification and grafting), enzymatically, or biotechnically treating native starch to change its properties [44].…”
Section: Modified Starchmentioning
confidence: 99%
“…Modified starch is prepared by physically (gelatinization, extrusion, foaming, and impregnation), chemically (esterification and grafting), enzymatically, or biotechnically treating native starch to change its properties [44]. Modified starches are commonly used as emulsifiers and stabilizers, viscosifying agents, coatings, and thickeners [45,46]. A study reported that starch chemical modification produces a biodegradable material with appropriate mechanical strength, flexibility, and water barrier properties to be used as packaging material [45,47].…”
Section: Modified Starchmentioning
confidence: 99%
See 1 more Smart Citation